2000
DOI: 10.1021/ie000553i
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Permeation through Crystalline Molecular Sieve Membranes

Abstract: The fluxes of aromatic molecules (p-xylene, o-xylene, and benzene) were measured as a function of temperature and feed partial pressure through several molecular sieve membranes (SAPO-5, SAPO-11, and mordenite) and three types of MFI membranes (silicalite-1, ZSM-5, and boron-substituted ZSM-5). Single-file diffusion appeared to control transport through the SAPO and mordenite membranes. Hence, those membranes showed ideal selectivities greater than 1 for benzene over the xylene isomers but no separation select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 57 publications
(136 reference statements)
4
44
0
Order By: Relevance
“…It is interesting to note this study did not provide any hint of further permeance increase at higher temperatures, as commonly quoted (gas activated transport) on different gases [8,9,[23][24][25] and also on xylenes [6,7,9,10]. This may be related to the support pore-plugging structure of the membrane, and will be detailed in another paper [26].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…It is interesting to note this study did not provide any hint of further permeance increase at higher temperatures, as commonly quoted (gas activated transport) on different gases [8,9,[23][24][25] and also on xylenes [6,7,9,10]. This may be related to the support pore-plugging structure of the membrane, and will be detailed in another paper [26].…”
Section: Discussionmentioning
confidence: 52%
“…Recent research efforts focus on using MFI-zeolite membranes for xylene separation, a potentially more energy-efficient separation method [5][6][7][8]. The MFI zeolite pore structure consists of straight, circular pores (0.54 × 0.56 nm), interconnected with sinusoidal, elliptic pores (0.51 × 0.54 nm) [9]. These pore sizes are close to the kinetic diameter of para-xylene (d k = 0.58 nm), and it is expected that its bulkier isomers (d k = 0.68 nm) would diffuse at a slower rate, and adsorb to a lesser extent in the MFI framework due to their size and shape [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have studied the separation of xylenes with MFI zeolite membranes demonstrating high permselectivity for p-xylene over the other isomers, attributed mainly to the preferential permeation of p-xylene, since the zeolite pores expose sterical hindrance for the permeation of the bulkier m-and o-xylene isomer molecules [104,221,[223][224][225]. In an outstanding study, Lai et al [226] reported on dramatic improvement of the p-/o-xylene separation by b-oriented silicalite-1 membranes.…”
Section: Product Removal: Enhanced Selectivity By Displacing the Chemmentioning
confidence: 99%
“…MFI zeolite membrane showed promising performance on organic separations, e.g., butane isomers and xylene isomers [4][5][6][7][8][9][10], while X-type and Y-type zeolite membrane showed good performance on carbon dioxide separation [11] and 1,3-propanediol separation [12]. The most significant progress was achieved by the A-type zeolite membrane in the pervaporation dehydration [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%